Conophylline Protects Cells in Cellular Models of Neurodegenerative Diseases by Inducing Mammalian Target of Rapamycin (mTOR)-independent Autophagy - Sasazawa, Yukiko (J Biol Chem, 2015)
Macroautophagy is a cellular response that leads to the bulk, nonspecific degradation of cytosolic components, including organelles. In recent years, it has been recognized that autophagy is essential for prevention of neurodegenerative diseases, including Parkinson disease (PD) and Huntington disease (HD). Here, we show that conophylline (CNP), a vinca alkaloid, induces autophagy in an mammalian target of rapamycin-independent manner. Using a cellular model of PD, CNP suppressed protein aggregation and protected cells from cell death caused by treatment with 1-methyl-4-phenylpyridinium, a neurotoxin, by inducing autophagy. Moreover, in the HD model, CNP also eliminated mutant huntingtin aggregates. Our findings demonstrate the possible use of CNP as a therapeutic drug for neurodegenerative disorders, including PD and HD.